KINERJA PERUSAHAAN: PENGARUH KARAKTERISTIK DEWAN DAN STRUKTUR KEPEMILIKAN - Anita, Anita; Fajriya, Nurkhalifa (Global Financial Accounting Journal, 2020)
The purpose of this observation was to empirically examine the effect of ownership structure and board characteristics on company performance. This observation used independent variables namely ownership concentration, state ownership, institutional ownership, managerial ownership, the board size, independent director, independent audit committee, audit committee meeting, and financial expert with the dependent variable as company performance. This observation used sample of 416 companies that are appropriate with the specified characteristics and are listed on the 2014-2018 Indonesia Stock Exchange. This observation analysis data used SPSS and Eviews version 10 programs. From the results of observations produced, the concentration of ownership, independent director, and independent audit committees have significant impact on company performance. While other variables such as state ownership, institutional ownership, managerial ownership, board size, audit committee meetings, and financial expert do not have impact that can affect company performance.